Mineral nutrition of tropical legumes: III. concentration and accumulation of macronutrients and dry matter digestibility "in vivo" of Leucaena leucocephala (LAM.) de Wit cv. Peru during a one year period - Silva, Denise Helu; Haag, Henrique Paulo (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1982)
The tropical leguminous olants are known as a high quality protein source and in some cases even as wood producers when dealing with the arbustive types. The leucena (Leucaena leucocephala (Lam.) de Wit cv. Peru) was noticed as a very promising species to the Brazilian cattle production, and this fact leads to the setting of a field experiment in order to know its nutrient demands. The experiment was carried out to obtain data for analysis of growth, concentration and extraction of macronutrients (N, P, K, Ca, Mg, S and the dry matter digestibility in vivo for the leaves relatad to the plant age. From the obtained data it was possible to verify that: The whole dry matter production is the highest when the plant was 360 days old. The largest increase in the leaf production in dry matter was observed from 240 days up to 360 days. The N and P concentrations decreased in leaves and stem along the plant life. An the other hand, the age of the plant did not affect the Ca concentration in the stem leaves not the Ca concentration in the stem. When the plants were 360 days old corresponding to the highest dry matter product ion period, the following contents in the leaves and stem were observed: Plants with 360 days also showed the macronutrients accumulations in the folowing order: N >; K >; Ca >; Mg >; >; S >; P. The digestibility of the dry matter in leaves is in the level of 51.05%, in 360 day old plants.